IBNU SINA DI MEJA KELAS DIGITAL: RELEVANSI PEMIKIRANNYA DALAM PENDIDIKAN MASA KINI - Muhammad Ridwan (Studia Religia : Jurnal Pemikiran dan Pendidikan Islam, 2025)
The purpose of this study is to describe the concept and method of education of Ibn Sina and examine its relevance to today's education system. This study employs a library research method with a qualitative approach to explore Ibn Sina's educational thought through written sources. Data were collected from primary sources, such as Ibn Sina's original works, and secondary sources, including books and scientific journals. The research applies content analysis to classify, interpret, and disseminate Ibn Sina's ideas within the context of modern education. The findings highlight Ibn Sina’s significant contributions to Islamic and Western education, particularly in medicine, philosophy, and logic, as demonstrated in his works such as Al-Syifa', Al-Najat, and Al-Qanun fi al-Thibb. His influence extended to medieval Europe, shaping intellectual traditions and influencing scholars like Thomas Aquinas. Furthermore, Ibn Sina’s holistic approach to education, which integrates intellectual and moral development, remains relevant today. His concepts of tiered education, adaptive curriculum, and effective teaching methods including talqin, demonstration, discussion, and apprenticeship continue to shape modern educational practices. This study reaffirms Ibn Sina’s enduring legacy as a foundational figure in both Islamic and Western educational thought. Keywords: Ibn Sina, educational thought, modern education.